Mixed emotions and credence service use: insights from at-risk gamblers. Issue 6 (2nd September 2021) - De Vos, Svetlana; Crouch, Roberta; Quester, Pascale; Ilicic, Jasmina
Abstract : Purpose: This paper aims to explore the power of appeals based on fear mixed with challenge co-designed with vulnerable consumers in motivating the use of credence services. Design/methodology/approach: A qualitative phase (Study 1), comprising focus groups of self-identified at-risk gamblers, revealed a series of conceptual themes for advertising stimuli that were then tested empirically (Study 2) on the likelihood to use credence services in a gambling context. Individual characteristics such as tolerance of ambiguity were also tested for their potential moderating influence. Findings: In comparison to appeals based on single emotions, fear mixed with the challenge has a significantly stronger impact on intentions to use credence services in at-risk gamblers. Findings confirm the indirect positive impact of fear mixed with the challenge via sequential mediators of involvement with advertising and attitude towards credence service advertising. The moderating role of tolerance of ambiguity on credence service use intentions was confirmed. Originality/value: The potential of a fear mixed with challenge appeal to motivate vulnerable consumers to seek credence services has not been investigated to date. The findings contribute to both the transformative service research and advertising literature streams by providing valuable insights into promotional campaigns aimed at vulnerable consumers such as at-risk gamblers.